Negative Effect of Current Account Surplus on Long-term Growth; Focused on the Cases of Japan, S. Korea and China - Choe, Yongshik; You, Seong-yop (Archives of Business Research, 2021)
It is a teaching of current economics that the surplus of current account in international payment contributes to the increase of income. But it has got a negative effect on the long-term growth in the reality, which is easily proved by some instances. First, the Japanese growth rate has been very low despite its current account maintaining a huge surplus. Second, it is another instance that South Korea has suffered from its low growth rate even if its government has enforced the policy to defend its exchange rate from declining while its current account surplus has become large since 1998. Next, the growth rate of China has decreased from the time when its foreign reserve has begun to reduce despite its huge surplus of current account. This paper clarifies the reason why their growths are stagnant despite their huge surpluses in current account. If this paper changes the policies of above countries, it would resolve their economic difficulties and settle the imbalance of the world economy. And this paper would contribute to the evolution of economics.